A new analytical model for ballistic waves generated by subsonic penetration in water. (15th November 2022) - Liu, Ting; Chen, Changhai; Cheng, Yuansheng
Abstract: A meticulous analytical investigation was conducted to better comprehend the characteristics of ballistic waves generated by subsonic penetration in water. In this study, a new analytical model was developed, in which a more reasonable distribution of source strength was considered. Ballistic experiments for a spherical projectile penetrating in a square tube were conducted to verify the new model, and better agreements were obtained between the experimental results and those predicted by using this new analytical model. Moreover, effects of projectile density, initial projectile velocity, and location of observation point on the characteristics of ballistic waves were systematically explored. Parameter studies reveal that the value of first pressure peak of ballistic waves varies linearly with v 0 2, and is close to a limit constant with the increase of projectile density. The amplitude of ballistic waves decreases with the increase of depth of observation point due to projectile deceleration, and the second pressure peak of ballistic waves disappears when the observation point is far away from the trajectory. The present analytical model can more accurately evaluate the pressure loads in hydrodynamic Ram due to subsonic penetration, and provide a significant guiding reference for precise design of fluid-filled defense structures. Highlights: A new analytical model for ballistic waves in water was established. A more reasonable distribution of source strength was considered. The prediction accuracy of ballistic waves model was substantially improved. The spatial characteristics of ballistic waves were more precisely illuminated.